Frequency of MYD88 and CD79B mutations, and MGMT methylation in primary central nervous system diffuse large B‐cell lymphoma. Issue 6 (30th August 2017) - Zheng, Mei; Perry, Anamarija M.; Bierman, Philip; Loberiza, Fausto; Nasr, Michel R.; Szwajcer, David; Del Bigio, Marc R.; Smith, Lynette M.; Zhang, Weiwei; Greiner, Timothy C.
Abstract : Primary CNS diffuse large B‐cell lymphoma (PCNS‐DLBCL) and systemic DLBCL harbor mutations in MYD88 and CD79B . DNA methyltransferase ( MGMT ) is methylated in some DLBCL. Our goal was to investigate the frequencies of these events, which have not been previously reported within the same series of patients with PCNS‐DLBCL. Fifty‐four cases of PCNS‐DLBCL from two institutions were analyzed by Sanger sequencing for MYD88 and CD79B, and pyrosequencing for MGMT . MYD88 mutations were identified in 68.8% (35 of 51 cases), with L265P being the most frequent mutation. Mutations other than L265P were identified in 21.6% of cases, of which eight novel MYD88 mutations were identified. Of mutated cases, 17.6% had homozygous/hemizygous MYD88 mutations, which has not been previously reported in PCNS‐DLBCL. CD79B mutations were found in six of 19 cases (31.6%), all in the Y196 mutation hotspot. MGMT methylation was observed in 37% (20 of 54 cases). There was no significant difference in median overall survival (OS) between the wild type and mutated MYD88 cases, or between methylated and unmethylated MGMT cases. However, a significant difference ( P  = 0.028) was noted in median OS between the wild type and mutated CD79B cases.